Description of five new species of Capitellidae (Annelida, Canalipalpata, Capitellida) from the coast of Chile (South America), and re-description of Mediomastus branchiferus Hartmann-Schröder, 1962 - Bick, Andreas; Zettler, Michael L. (Zootaxa, 2026)
During an expedition with the research vessel SONNE in January 2023 eight stations along an oxygen gradient off Chile (36 °S) were sampled to investigate the differences in species composition along the gradient. This study describes all Capitellidae found at these stations at water depths between 56 and 912 metres. A total of five species were found that were previously unknown. These species are Dodecamastus branchiphorus sp. nov., Leiochrides chilensis sp. nov., Mediomastus concepcionensis sp. nov., Notomastus carlvilhelmi sp. nov. and N. friedrichi sp. nov. These species are described, illustrated and compared with all known species of the respective genera. In this context, the observed variability of the features that are considered important for the characterization of genera and species of Capitellidae is also discussed. The distribution of these species in relation to water depth, oxygen content, sediment and temperature is described and discussed. Mediomastus branchiferus Hartmann-Schröder, 1962, currently considered a taxon inquirendum, is described and illustrated on the basis of type material, and can now be recognized as a valid species again based on the presence of branchiae and other specific characteristics. The occurrence of a larval stage (manca) of an unknown Tanaidacea species in the abdomen of Notomastus carlvilhelmi sp. nov., is also illustrated and described.